A free vascularized fibular graft for reconstruction of mandibular bony defect following excision of odontogenic keratocyst - Ibrahim, Farzana B; Hassan, Shamim; Hasan, Sajid; Anwar, Raihan; Islam, Md Rashedul (IMC Journal of Medical Science, 2017)
We present a case of reconstruction of a bony defect due to the excision of recurrent mandibular odontogenic keratocyst in a 45 years old diabetic male. Free vascularized fibular composite graft was taken from the contra lateral lower leg to reconstruct the defect. A two team approach consisting of plastic and maxillofacial (MF) surgeon was adopted. The functional and aesthetical outcome was satisfactory and bone healing occurred without any major complication. IMC J Med Sci 2017; 11(2): 70-72